Abiotic mediation of common ions on the co-exposure of CeO2 NPs with Sb (III) or Sb (V) to Glycine max (Linn.) Merrill. (Soybean): Impacts on uptake, accumulation and physiochemical characters. (December 2020) - Cao, Weicheng; Gong, Jilai; Zeng, Guangming; Song, Biao; Zhang, Peng; Li, Juan; Fang, Siyuan; Tang, Siqun; Qin, Lei; Ye, Jun; Cai, Zhe
Abstract: With the most active Sb mines, the "dominance" on Sb production of China lead to increasingly release and omnipresence of Sb in environment through mining activities as well as the life cycle of Sb-containing productions. The introduction of engineered nanoparticles (ENPs) accidentally or intentionally (such as NP-containing sludge as fertilizer) might increase the probability of co-exposed with Sb to plants. In this study, CeO2 NPs, one of the most widely used nanomaterials in industries with potential oxidizing or reducing properties, was selected and co-exposed with Sb (III) or Sb (V) to investigate their mutual effects on uptake, accumulation and physiological effects in soybeans. The results showed that CeO2 NPs increased the Sb (III) and Sb (V) concentrations in roots by 36.7% and 14.0% respectively, while Sb (III) and Sb (V) inhibited the concentration of Ce in roots by 97.1% and 86.9% respectively. In addition, the impacts of extra common ions (Mn 2+, Cu 2+, Fe 3+ and Zn 2+ ) on the fate of Ce and Sb in soybeans in co-exposure of CeO2 NPs with Sb were investigated as well. Mn 2+ and Fe 3+ increased the accumulations of Ce and Sb (III) in the co-exposure of CeO2 NPs with Sb (III), but reduced that in the co-exposure of CeO2 NPs with Sb (V). Notably, the addition of Cu 2+ and Zn 2+ consistently increased the uptake and accumulation of Ce and Sb in the co-exposure treatments. Moreover, the effects of Sb on the dissolved portion of CeO2 NPs in soybean roots were also investigated. This study provided a perspective that extra ingredient (mineral elements, organic element or other nutrients) might regulated the interactions in ENPs-heavy metals-plants system which need further explorations. Graphical abstract: Image 1 Highlights: Sb (III) and Sb (V) significantly reduced Ce accumulation whereas CeO2  NPs only reduced Sb (III) uptake by soybean. Mn 2+  had no significant effects on Ce and Sb accumulation in roots but increased Sb translocation into stems and leaves. Fe 3+  inhibited the accumulation of Sb (V) and Ce while Cu 2+  and Zn 2+  increased the uptake of Ce and Sb significantly. Mn 2+ /Fe 3+  and Cu 2+ /Zn 2+  might operate through Mn/Fe-(hydro) oxides and transpiration driving force respectively. Abstract : The impacts of co-exposure of CeO2 NPs with Sb to soybeans, as well as the translocation and accumulation of Ce and Sb, could be regulated by the addition of different common ions.